DETERMINATION OF RATE CONSTANT AND STABILITY OF ADSORPTION IN COMPETITIVE ADSORPTION OF Cr(III) AND Cd(II) ON HUMIC ACID BY USING THE NEW MODEL OF KINETIC FORMULATION - Suyanta Suyanta; Sri Sudiono; Sri Juari Santosa (Indonesian Journal of Chemistry, 2004)
Determination of rate and stability constants of adsorption in competitive adsorption of Cr(III) and Cd(II) on humic acid by using the new model of kinetic formulation has been done. The new model based on assumption that those adsorption was first order adsorption rearched equilibrium.Humic acid was isolated from Peat moss of Silaut- West Sumatra by modificated Schnitzer method. Humic acid characterization was conducted by using infrared spectrophotometer with KBR pellet method. The experiment of kinetic adsorption was conducted in batch system reactor using erlenmeyer at 25 ± 0.01 oC of water steam bath and in a series of sampling procedure. Initial concentration of both Cr(III) and Cd(II) was 4x10-4 M. Thirty milligrams of humic acid was added to 200 mL of metal solution, and then stirred continuously. At the fixed periode of time, 10 mL of sample was taken using a syringe, then filterd with 0.45 µm filter paper. Concentration of Cr(III) and Cd(II) in the filtrate was determinated by AAS, while that was adsorbed by humic acid was equal to difference between initial and equilibrium concentration. It was concluded that competitive adsorption of Cr(III) and Cd(II) on humic acid was first order adsorption rearched equilibrium as proposed in this research. Adsorption rate constant of Cr(III) on humic acid  at competitive condition was greater than of Cd(II), but on the contrary for stability constant (K). Competition between Cr(III) and Cd(II) to interact with the active side of humic acid was dominated by Cr(III).